A Rare Case of a Traumatic Posterior Hip Dislocation in a 3-Year-Old Boy: A Case Report and Review of the Literature. (9th March 2020) - Clausen, Jan-Dierk; Winkelmann, Marcel; Macke, Christian; Mommsen, Philipp; Krettek, Christian; Brand, Stephan
Abstract : We present a rare case of neglected hip dislocation in a 3-year-old boy. Hip dislocations in childhood represent less than 6% of all injuries. The boy presented to the ED with ongoing hip pain after his leg got stuck in a carousel. The physical and radiologic examination revealed a posterior right hip dislocation. The closed reduction failed, so open reduction during surgery was performed. The postoperative protocol included 3 days of immobilization with early mobilization and pain-adapted weight bearing. No signs of femoral head malperfusion occurred 2 months after the injury. The patient did not complain of any limitations such as weight bearing problems or loss of range of motion. In comparison to adults, there are several specialties such as the fact that minor trauma can lead to hip dislocations due to the laxity of the ligaments, and due to the limited direct anamnestic options, neglected hip dislocations can occur. The treatment should focus on immediate proper reduction. The main complications after traumatic hip dislocation are avascular necrosis of the femoral head, redislocation, and early osteoarthritis.